Literacy of Pension Fund Practice in Indonesia - Boma, Kukuh Dwi; Hidayat, M; Putra, Yananto Mihadi (Economics & Islamic Finance Journal (ECIF), 2024)
This article discusses the practice of pension funds in Indonesia, covering historical developments, current challenges, and obstacles arising from government regulations and other social aspects. This article explores the evolution of pension funds, the legal framework that governs their operations, and the socioeconomic factors that influence their growth. Key challenges include regulatory barriers and the need to increase public awareness. This study contributes to the understanding of how pension funds can better serve the elderly population in Indonesia.